Anomalous values and missing data in clinical and experimental studies - Miot, Hélio Amante [UNESP] (FapUNIFESP (SciELO), 2019)
During analysis of scientific research data, it is customary to encounter anomalous values or missing data. Anomalous values can be the result of errors of recording, typing, measurement by instruments, or may be true outliers. This review discusses concepts, examples and methods for identifying and dealing with such contingencies. In the case of missing data, techniques for imputation of the values are discussed in, order to avoid exclusion of the research subject, if it is not possible to retrieve information from registration forms or to re-address the participant.
Valores anômalos e dados faltantes em estudos clínicos e experimentais
Keywords: Data analysis; Database; Multiple imputation; Outlier